Comparison of carbopol 934 and 941 as thickeners on ketoconazole microemulsions based on physical stability - Pramulani Mulya Lestari; Kori Yati; Nanda Savira (Pharmaciana, 2018)
As a drug delivery system, ketoconazole microemulsion in virgin coconut oil (oil phase) is added with a thickening agent to create transdermal dosage form. This study aimed to compare the physical stabilities of ketoconazole microemulsions formed with different thickeners, namely Carbopol 934 and Carbopol 941. The formula used varying concentrations of Carbopol 934 and Carbopol 941, i.e., 0.15% and 0.25%. The stability was observed during eight-week storage in which the conditions were controlled by different degrees of temperature, i.e., 40C, 25-300C (room temperature), and 400C. The stability tests included organoleptic observation, pH, surface tension, viscosity, particle size, and zeta potential. Based on the Kruskal-Wallis test results, ketoconazole microemulsion with Carbopol 941 that had been stored in different temperature showed a significant difference in particle size (significance value< 0.05), but it did not apply to Carbopol 934. The evaluation revealed that compared to 0.25% of Carbopol 934, microemulsion with 0.15% of Carbopol 934 had a smaller difference between the time intervals. This research concluded that the use of 0.15% of Carbopol 934 as a thickener in ketoconazole microemulsion had better physical stability compared to Carbopol 941 due to the influence of temperature and length of storage.